The Effectiveness of the Reciprocal Teaching Learning Model Based on Multiple Intelligences (MI) on Student Learning Outcomes in Class VIII Vibration, Waves and Sound Material - Saida, Lailatus; Auta, Ali (Schrödinger: Journal of Physics Education, 2023)
Purpose of the study: This study aims to determine the effectiveness of the reciprocal teaching learning model based on multiple intelligences on the learning outcomes of students on vibration, waves and sound in class VIII Junior high school.Methodology: This research is experimental research conducted in junior high schools. The sample in this research was class VIII junior high school students. The sampling technique was carried out using a saturated sampling technique. Data collection uses the test method (multiple choice test) to obtain data about learning outcomes. Test the research hypothesis using the t-test.Main Findings: Based on t test calculations with a significance level of 5%, tcount = 3.01 while ttable = 1.994. Because tcount > ttable means that the average physics learning outcomes of students who are taught using the multiple intelligence-based reciprocal teaching learning model are effective on student learning outcomes. So, it can be concluded that learning using the reciprocal teaching learning model based on multiple intelligences on vibration, wave and sound material is effective on the learning outcomes of class VIII students in junior high schools.Novelty/Originality of this study: This research makes an important contribution in understanding how various learning strategies can be adapted to the individual needs and intelligence of students to improve their learning outcomes in complex material such as Waves, Vibrations and Sound.